the Influence of Tourism Potential, and Promotion on the Decision to Visit Beejay Bakau Resort (BJBR) Probolinggo City - Rr. Setyani Hidayati; Seger Priantono; Ainiyah Damayanti (Jurnal Ilmiah Jendela Pendidikan, 2022)
This study aims to determine the influence of tourism and promotion potential on visiting the Beejay Bakau Resort (BJBR) Probolinggo City. This research focuses on the problem of promoting the existence of tourism with various tourist products is not an easy thing. It is necessary to consider the use of promotional media that will be used so that tourists are interested, influenced, and make decisions to visit. The type of research used is quantitative research with an associative approach that is causal. The data collection method used was primary data and secondary data obtained from a questionnaire of 60 people or respondents. The sampling method uses nonprobability sampling with a simple incidental sampling technique. Hypothesis testing is carried out using simultaneous tests and partial tests. The results showed that tourism and prromosi potential simultaneously influenced the decision to visit BeeJay Bakau Resort (BjBR) Probolinggo City, and tourism and promotion potential partially influenced the decision to visit BeeJay Bakau Resort (BjBR) Probolinggo City.